Impact Of English Language Learning On Mental Health: Exploring The Relationships Between Language Anxiety, Self-Esteem, And Depression - Shami, Shifa; Parimala Venu, Capt. Dr. V; Shanampoodi, Gandhi Babu; Rajeswari, T.S.; Chaithanya, D.; Fazulur Rehmana, Shaik Shakira; Sharma, Samiksha (Journal of Neonatal Surgery, 2025)
Learning a second language, especially English, has significant implications for mental health. This paper explores the relationship between English language learning (ELL), language anxiety, self-esteem, and depression. While English proficiency offers social and professional advantages, it can also contribute to stress and emotional distress, particularly among non-native learners. Language anxiety, stemming from communication difficulties and fear of judgment, can negatively impact self-esteem and lead to depressive symptoms. Conversely, successful language acquisition can enhance confidence and mental well-being. This study examines existing literature on ELL’s psychological effects and provides recommendations for minimizing negative impacts while maximizing the mental health benefits of language learning.